Implied licences in copyright law - Mysoor, Poorna (Oxford University Press, 2021)
This book develops a systematic way of implying copyright licences and analyses the existing case law in light of these proposed frameworks to demonstrate how the court's reasoning can be made methodical and transparent, testing the methodology in relation to three essential functions on the internet - browsing, hyperlinking, and indexing.